Greater adherence to a Mediterranean-like diet is associated with later breast development and menarche in peripubertal girls. Issue 6 (23rd April 2020) - Szamreta, Elizabeth A; Qin, Bo; Rivera-Núñez, Zorimar; Parekh, Niyati; Barrett, Emily S; Ferrante, Jeanne; Lin, Yong; Bandera, Elisa V
Abstract: Objective: To examine adherence to a Mediterranean-like diet at age 9–10 years in relation to onset of breast development (thelarche) and first menstruation (menarche). Design: We evaluated the associations of adherence to a Mediterranean-like diet (measured by an adapted Mediterranean-like Diet Score, range 0–9) with thelarche at baseline, age at thelarche and time to menarche. Data were collected at baseline during a clinic visit, complemented with a mailed questionnaire and three 24 hour telephone dietary recalls, followed by annual follow-up questionnaires. Multivariable Poisson regression, linear regression and Cox proportional hazards regression were used to evaluate timing of pubertal development in relation to diet adherence. Setting: New Jersey, USA. Participants: Girls aged 9 or 10 years at baseline (2006–2014, n  202). Results: High Mediterranean-like diet adherence (score 6–9) was associated with a lower prevalence of thelarche at baseline compared with low adherence (score 0–3; prevalence ratio = 0·65, 95 % CI 0·48, 0·90). This may have been driven by consumption of fish and non-fat/low-fat dairy. Our models also suggested a later age at thelarche with higher Mediterranean-like diet adherence. Girls with higher Mediterranean-like diet adherence had significantly longer time to menarche (hazard ratio = 0·45, 95 % CI 0·28, 0·71 for high v . low adherence). Further analysis suggested this may have been driven by vegetable and non-fat/low-fat dairy consumption. Conclusions: Consuming a Mediterranean-like diet may be associated with older age at thelarche and menarche. Further research is necessary to confirm our findings in other US paediatric populations and elucidate the mechanism through which Mediterranean-like diet may influence puberty timing.